2015
DOI: 10.1038/nprot.2015.017
|View full text |Cite
|
Sign up to set email alerts
|

High-yield and high-purity isolation of hepatic stellate cells from normal and fibrotic mouse livers

Abstract: Hepatic stellate cells (HSCs) have been identified as the main fibrogenic cell type in the liver. Hence, efforts to understand hepatic fibrogenesis and to develop treatment strategies have focused on this cell type. HSC isolation, originally developed in rats, has subsequently been adapted to mice, allowing to study fibrogenesis by genetic approaches in transgenic mice. However, mouse HSC isolation is commonly hampered by low yield and purity. Here we present an easy-to-perform protocol for high-purity and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
362
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 435 publications
(380 citation statements)
references
References 26 publications
(27 reference statements)
3
362
0
1
Order By: Relevance
“…We isolated Thy1 MCs as mentioned above from normal mouse liver, and HSCs were subsequently collected from the remaining NPC flow‐through by density‐gradient centrifugation owing to their abundance of retinoid‐storing lipid droplets 25. Isolated Thy1 MCs contained no apparent lipid droplets, which were characteristic of HSCs observed under the phase‐contrast microscope (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We isolated Thy1 MCs as mentioned above from normal mouse liver, and HSCs were subsequently collected from the remaining NPC flow‐through by density‐gradient centrifugation owing to their abundance of retinoid‐storing lipid droplets 25. Isolated Thy1 MCs contained no apparent lipid droplets, which were characteristic of HSCs observed under the phase‐contrast microscope (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cells were isolated according to Mederacke et al, [30] with the relative modifications for human liver. [31] Briefly, 10 g of total human liver tissue was digested with 0.01% Collagenase, 0.05% Pronase and 0.001% DNase I without performing perfusion.…”
Section: In Vitro Studies In Human Hscmentioning
confidence: 99%
“…However, a systematic procedure for the simultaneous isolation and purification of multiple liver cell populations has only been reported in two previous studies [Liu et al, 2011;Pfeiffer et al, 2014]. Currently, the simultaneous isolation of HCs and NPCs is mainly based on the separation of HCs by low-speed centrifugation [Liu et al, 2011;Pfeiffer et al, 2014] and, as described below, the most common approach to purifying single NPCs is based on cell density [Alpini et al, 1994;Tacke and Weiskirchen, 2012;Mederacke et al, 2015]. The cell densities of LSECs and KCs have some overlap.…”
Section: Introductionmentioning
confidence: 99%
“…HCs may aggregate with NPCs in subsequent centrifugation steps, thereby increasing the centrifugal density of NPCs and altering the purity and yield of the isolated liver cells [Knook et al, 1982;Alpini et al, 1994]. Therefore, a previous study suggested the administration of nonspecific protease (pronase) through the portal vein during perfusion to selectively lyse HCs for the exclusive isolation of NPCs [Knook and Sleyster, 1976;Alpini et al, 1994;Maschmeyer et al, 2011;Mederacke et al, 2015]. However, this resulted in the loss of HCs.…”
Section: Introductionmentioning
confidence: 99%